PROVIDING SUPPLEMENTARY FOOD TO NUTRITIONAL CHILDREN AND APPLICATION OF FOOD PROCESSING PROCESS TECHNOLOGY AND ECONOMIC EMPOWERMENT - Purba, Rasita; Efendi, Hidir (Journal of Community Research and Service, 2022)
Abstract” Fish has good potential to overcome malnutrition problems such as lack of energy and protein (PEM), lack of vitamin A, disorders due to lack of iodine, and nutritional anemia, while tempeh-based formulas can shorten the duration of acute diarrhea and accelerate weight gain after suffering from one illness. episodes of acute diarrhea. Tempe and fish are easier to digest because of their high content of free fatty acids, peptides, and amino acids. The objectives of this IbM activity are (1) the design of more spin machines, (2) the production of forte cookies and fish meal cookies, (3) the production of various processed fish, packaging, and nutritional status. Specific targets to be achieved; There are variations of PMT Toddlers to improve the nutritional status of toddlers, production of processed fish through the application of food processing technology, packaging, and economic empowerment of fishing communities. The approach method used is the method of education, production training, business management training, design, and assistance. The results of this IbM program activity are more spin machines with a drying capacity of 10 kg/30 minutes, additional food products (PMT) for toddlers in the form of forte cookies, fish flour cookies, and various processed fish products. Conclusion: Organoleptic tests for taste, aroma, texture, and color, showed positive responses from IbM partners and participants, as well as responses from local people who tasted the product. The nutritional knowledge of the cadres is good (87.3%), making forte and fish meal (91%), making various kinds of processed fish (91.6%). The nutritional status of children under five is still under the category of malnutrition (36%). Selling processed fish products is still (28%). The production of a variety of processed fish products will be an opportunity for new entrepreneurs for posyandu cadres and fishing communities to increase the income of fishing communities.